Effects of natural ageing on macroscopic physical and mechanical properties, chemical components and microscopic cell wall structure of ancient timber members. (12th December 2022) - Xin, Zhenbo; Fu, Ruiyun; Zong, Yuanyuan; Ke, Dongfang; Zhang, Houjiang; Yu, Yongzhu; Zhang, Wenbo
Highlights: Effects of natural ageing on the properties of ancient timber members. Macroscopic properties, chemical components and microstructure of aged timber considerably changed. Mechanical properties decreased with natural aging. Abstract: The main objective of this study was to investigate the effects of natural ageing on macroscopic physical and mechanical properties, chemical components, and microscopic cell wall structure of larch ( Larix principis-rupprechtii Mayr ) and nanmu ( Phoebe zhennan S. Lee ) timber members in ancient architecture. In this work, aged larch and nanmu timber members were obtained from the restoration architecture and their ages were determined based on accelerated mass spectrometer 14 C method. Macroscopic physical, mechanical properties and chemical components were tested and determined of each timber members; meanwhile, the microstructural changes of cell wall were observed by scanning electron microscope (SEM). Finally, Pearson's correlation analysis was conducted to reveal the relationships among them. The results indicated that natural ageing has a significantly effect on the macroscopic physical and mechanical properties, chemical components, and microscopic cell wall structure. First, equilibrium moisture content (EMC), the coefficient of wet swelling coefficient (SW) and colour parameters considerably changed of larch and nanmu timber members with aging years. Mechanical property parameters of larch timber show a significant decrease, and the changes of chemical components and microstructure of cell structure of nanmu specimens indicates the mechanical property parameters decreased. Further, the relative contents of cellulose and hemicellulose were significantly reduced, obvious damage and deformation were observed in the cell wall of larch and nanmu timber specimens. The results explained the change of macroscopic physical and mechanical properties, especially negative effects on mechanical properties. It was concluded that the relative contents of cellulose and hemicellulose were decreased, and the microstructure was damaged under the natural ageing effect, resulting in a decrease in mechanical properties with an increase in colour properties and dimensional stability.